Sociodemographic, clinical and obstetric characteristics of women with acute kidney injury in the pregnancy-puerperal cycle: a case series - Itana Souza; Leila Katz; Isabela Coutinho; Melania Amorim (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Introduction: to report cases of women with acute kidney injury (AKI) in the pregnancy-puerperal cycle, admitted to a maternity teaching hospital in Recife, Pernambuco, Brazil. Description: a case-series study reviewing the records of 100 patients with AKI admitted to the maternity hospital of the Institute of Integrative Medicine Professor Fernando Figueira (IMIP - Portuguese acronym). Discussion: the majority of patients (65.1%): were brown-skinned and the mean age was 25.5years; were primiparas (65.1%) and had cesarean section (75.5%). The most common hypertensive disorder was preeclampsia (74.0%), followed by chronic arterial hypertension (11.0%) and eclampsia (6.0%). Hemorrhage occurred in 19% of women. The most common form of treatment was fluid therapy (70.0%) and oliguria was one of the most common AKI consequences (84.8%). Hemodialysis was necessary in 13% of cases and 4.0% died. Kidney function was restored prior to discharge from hospital in almost 70.0% of cases. The main causes of AKI were hypertensive disorders and hemorrhage/hemorrhagic shock.